Populasi dan Keanekaragaman Fungi Mikoriza Arbuskular pada Rizosfir Tanaman Lada Monokultur dan Polikultur - Sari, Oktafia; Rini, Maria Viva; Evizal, Rusdi; Karyanto, Agus (Universitas Lampung, 2024)
Arbuscular mycorrhizal fungi (AMF) is a type of fungus that comes from the endomycorrhizal group, these fungi have the ability to form symbiosis with almost 90% of higher plant species. Population and diversity of AMF are influenced by biotic factors and abiotic factors. This research aims to determine the differences in population, diversity and dominant types of AMF in the rhizosphere of pepper planted in monoculture and pepper in polyculture. The soil samples were taking from monoculture and polyculture pepper plantations in Air Naningan District, Tanggamus Regency. The AMF population was tested using the One way Annova test. Culture trapping was done using a factorial treatment with the first factor being the origin of the soil sample (K) and the second actor being the type of host plant (T). Treatments design used was randomize design (CRD). The results showed that the AMF population in polyculture pepper plantation soil samples was higher than monoculture pepper, based on the Shannon-Wiener Diversity Index, AMF diversity in monoculture pepper and coffee intercropping pepper plantations was higher than in cocoa intercropping pepper plantations, and the type of AMF was dominant. from the results of trapping culture with monoculture pepper garden soil samples, namely spores of the species code S7, in samples of coffee intercropping pepper plantations the code S7 is dominant, while in cocoa intercropping pepper plantations it is dominated by code S6. Keywords: Arbuscular mycorrhizal fungi, diversity, population.